The Silk Route as an Economic Artery: Reassessing Its Transformative Impact on Medieval India’s Commercial Landscape, fiscal systems and economic policy. - Khalid Bashir,; Ishfaq Ahmad Mir (Journal of International Islamic Law, Human Right and Public Policy, 2025)
The Silk Route was not merely an avenue for luxury trade but also a vibrant economic force that rebuilt medieval India's commercial and fiscal systems. This study revises its contribution to urbanization, monetization, and state economic policy, countering Eurocentric assumptions minimizing India's place in transregional trade. Based on numismatic evidence, travelogues, and GIS mapping, it indicates the prosperity of cities like Mathura, Taxila, and Delhi as significant trade centers, successfully integrating Persian, Central Asian, and Chinese networks. In addition, the study considers disruptions, such as Mongol invasions, forcing a strategic realignment toward Indian Ocean trade, thus perpetuating India's prolonged commercial dominance.